Analisis Sentimen Masyarakat Terhadap Kualitas Layanan Rumah Sakit Indonesia Menggunakan Algoritma Text Mining dan TF-IDF - Zahra, Aulia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Service at the hospital is a very important thing that must be obtained by every patient, both BPJS patients and patients with public fees.  Patient satisfaction depends on the quality of service provided by the hospital.  Service is all the efforts made by all employees at the hospital to meet patient satisfaction.  Patient satisfaction is also an assessment that will be obtained by the hospital.  If the patient gets good service then the hospital will get a good rating, and if the patient gets bad service then it is not impossible for the hospital to get a bad rating. Based on comments submitted by the public on social media regarding the quality of hospital services in Indonesia, it has become a benchmark for related parties so that they can monitor and try to improve the quality of hospital services throughout Indonesia and understand the needs and desires of patients so that people can experience good service. Therefore  , sentiment analysis using the text mining algorithm and TF-IDF aims to find out how the public is satisfied with the quality of hospital services in Indonesia which will be categorized into positive and negative sentiments. After carrying out the process using the text mining algorithm and TF-IDF by following the research series and stages, sentiment analysis based on 50 comment data regarding the Quality of Hospital Services in Indonesia obtained results with a positive sentiment of "35.36" % and a negative sentiment of "64",  63" %.